SUSTAINABLE MANAGEMENT OF ELECTRICITY - PRACTICES OF FEDERAL UNIVERSITY OF LAVRAS - Ferreira, Silvia Costa; Rezende, Marcelo Arriel; da Silva, Joaquim Paulo; Della-Sávia Braga, Isadora Nascimento (UI Scholars Hub, 2021)
Considering that most of the world electrical matrix is made up of non-renewable sources, the search for safer and more sustainable energy generation solutions has grown. In view of this scenario, there is an increase in the use of renewable energy sources integrated with electrical systems. In this context, Universities have an important role in research development, implementation of environmental plans aimed at sustainability, optimization in the use of electric energy and development of the use of renewable energies. The Federal University of Lavras has an environmental plan with goals related to carbon emissions, solid waste management, rainwater collection and reuse, among others, are established. In order to achieve the goals related to sustainable electricity management practices on campus, the University has acted in several ways, resulting in approximately 30% electricity savings. This article presents the actions of the University in obtaining this result. First, we present a study on the application of energy indicators as a strategic tool to assist in the management process at the Federal University of Lavras (UFLA). Next, we discuss the energy efficiency projects developed in conjunction with the local concessionaire (CEMIG) and their impact on energy consumption. Finally, we present the proposal for the implantation of a microgrid in the internal distribution network and detail the photovoltaic generation system already installed. The evaluation of the energy indicators allowed the definition of priorities for the allocation of investments in the energy efficiency program. In addition, the results were compared to the goals outlined in environmental plan of the university. Finally, the ongoing microgrid project is presented but, to date, there are no significant data on the generation of UFLA's Solar Parking.